On Stories of Liveliness: following the Arts of Living on a Damaged Karoo Veld - Köster, Terena (Social Anthropology, 2020)
This thesis is concerned with the conditions of generating a livable Karoo landscape and the arts of living on a damaged Karoo veld. It takes place in a context where the anthropogenic influences on land degradation, desertification and biodiversity loss continues to haunt the Karoo in the present. The Karoo is a semi-arid region that spans the interior of South Africa. It is also region that has been subject to ongoing and widespread concern of the impact of overgrazing, threatening the livability of the Karoo landscape. This is a result of human/nonhuman relations that have been grounded in a colonial mastery of the land, whereby the advent of private property regimes, modernist technologies and capitalist extraction has allowed for the land to be cheapened, exhausted and severely degraded in a process of colonial dispossession. This research is a qualitative ethnography interacting with farmers and nonhumans on rangelands in the Great Karoo. This thesis shows how the earlier degradation of the Karoo has demanded farmersto pay attention to the relationalities between ecology and economy, since their economic/ecological survival depends entirely on the ongoing multispecies assemblages of which humans form a part. Infrastructures and technologies have become grounds for new ontological practices of regenerating the Karoo veld. Infrastructures (namely fencing) and sheep are used in ways that mimic the earlier migration of large herds of antelope. Here, the bodies of sheep are curated and moved in order to perform a particular ordering of a Karoo ‘nature’. This movement is believed to instigate multispecies liveliness. Sheep, who were once destroyers of the veld, are now enrolled in practices that are believed to bring back the ‘natural’ vegetation of the Karoo. The thesis problematises the ongoing Western ways of knowing that separate the world into binaries of ‘nature’/’culture’, ‘human’/’non-human’, ‘subject’/object’, ‘domestic’/‘wild’, ’economy’/‘ecology’, ‘life’/‘death’. Rather, it argues that a concern with ontological plurality is a process of paying attention to the mutual ecologies and multiple species that gather in human/nonhuman worlding projects on rangelands in the Karoo.